Pelatihan Penulisan Artikel Kepada Anggota Hima Prodi Ilmu Komunikasi K. Pangandaran Unpad untuk Meningkatkan Kualitas Konten Website Prodi - Dwi Masrina; Rizal Azizul Haqiem; Renaldi Maulana Yusuf; Thalia Zahra Ashifa (JPM: Jurnal Pengabdian Masyarakat, 2023)
The objective of the article writing training provided to the members of Hima Prodi Communication Science, K. Pangandaran Unpad, is to enhance the quality of the website content managed by Prodi Ilmu Komunikasi K. Pangandaran Unpad. The website currently does not have any official contributors, hence the quantity and quality of the content is still lacking. This article will discuss the article writing training process, from the creation of the articles to the management of the website with the latest content, in order to promote important information for the academic community. The methods used to achieve this goal include group coordination, coverage of activities, material presentation, mentoring, and publication of articles. The result of this activity is the continuity of the website through the publication of articles or press releases created by the members of Hima Ilmu Komunikasi K. Pangandaran Universitas Padjadjaran via the Prodi Ilmu Komunikasi K. Pangandaran website. Moreover, through this training, the writing skills of the students will improve over time through frequent coverage and article writing for the website.